PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI MELALUI MEDIA GAMBAR BERSERI PADA SISWA KELAS V SD NEGERI PASIR AWI KABUPATEN TANGERANG - Siti Nurul Umayroh; Muhammad Soleh Hapudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Picture series media is suitable for use at Pasir Awi Public Elementary School in Tangerang Regency because teachers still use the lecture method in teaching. As a result, students are less actively engaged and less interested in participating in Indonesian language lessons. Furthermore, student learning outcomes show that less than 50% have not achieved mastery based on the Minimum Completion Criteria (KKM). This research method is a classroom action research (Classroom Action Research) conducted in two cycles. Each cycle consists of four meetings. The purpose of this study is to determine the improvement of narrative writing skills through the use of picture series media. The research procedure includes the stages of planning, implementation, observation, and reflection. The research subjects were 34 fifth-grade students. Data collection techniques were carried out through observation, testing, and documentation. Data were analyzed quantitatively and qualitatively. The results of the study showed that in cycle I, the average value of student learning outcomes was 61.18. In cycle II, the value increased significantly to 75.82, which is classified as high category from the ideal value of 100. Learning completeness also increased, from only 3 students (8.82%) in cycle I to 30 students (88.24%) in cycle II. Classical learning completeness was achieved because more than 80% of students had met the KKM. Thus, learning using serial picture media was proven effective in improving narrative writing skills and the implementation of the action was stopped in cycle II because it had achieved the learning target. Evaluation of the results of this study indicates that image series media can increase student participation, stimulate writing interest, and help them express ideas coherently. However, for optimal results, teachers need to adjust the image selection to suit the theme and engage students in discussions before writing.